Effect of Liquamycin® and Syntabac Plus® on gain and health of stockers purchased as steers or bulls - F. Brazle; Gerry L. Kuhl (Kansas Agricultural Experiment Station Research Reports, 1989)
Steer calves gained faster (P<.001) and required fewer treatments per animal (P<.01) than newly castrated bull calves during a 29-day receiving period. Liquamycin® (LA-200) injection at arrival increased steer gains (P<.08) and reduced treatments required per animal (P<.08). The combined use of LA-2oo and Syntabac Plus®"¢ increased gains (P<.08) of newly castrated calves.
Keywords: Cattlemen& #x27; s Day; 1989; Kansas Agricultural Experiment Station contribution; no. 89-567-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 567; Beef; Liquamycin®; Syntabac Plus®; Stockers